Habbecik Pompalı Absorbsiyonlu Sistemlerin Termodinamik Analizi - Boylu, Yeşim (Fen Bilimleri Enstitüsü, 2012)
Dış enerji kaynağı olarak her türlü ısıl enerjiyi kullanabilen absorbsiyonlu sistemler, özellikle enerji ihtiyacının arttığı son yıllarda oldukça cazip hale gelmiştir. Ayrıca, absorbsiyonlu sistemlerde çalışma akışkanı olarak ozan tabakasına zarar vermeyen doğal akışkan çiftleri kullanılmaktadır. Bu sebeple absorbsiyonlu sistemler çevre ile dost sistemlerdir. Absorbsiyonlu sistemler bulundurdukları elemanlar ve çalışma prensiplerinde olan farklılıklar sebebiyle bir çok çeşide ayrılmıştır. Klasik absorbsiyonlu soğutma sistemleri, buhar sıkıştırmalı soğutma sistemlerine oldukça benzerdir. Buhar sıkıştırmalı soğutma sisteminden farklı olarak, kompresörün yerini termal sıkıştırıcı olarak adlandırdığımız soğurucu, kaynatıcı, saflaştırıcı ve eriyik ısı pompasından oluşan karmaşık bir mekanizma almaktadır. Buhar sıkıştırmalı soğutma sistemleri ile benzer olarak sistem elemanları arasında aynı zamanda yoğuşturucu ve buharlaştırıcı bulunmaktadır. Yapılan bu tez çalışması kapsamında klasik absorbsiyonlu sistemlerden farklı olarak, absorbsiyonlu sistemlerin bir çeşidi olan habbecik pompalı absorbsiyonlu sistem, literatürdeki ismiyle diffusion absorption refrigeration , incelenmiştir. Bahsi geçen bu sistem klasik absorbsiyonlu sistemden farklı olarak herhangi bir pompa elemanı bulundurmamaktadır. Pompa yerine sistem içerinde sirkülasyonu sağlamak için habbecik pompası kullanılmaktadır. Aynı zamanda sistemde buhar sıkıştırmalı ve klasik absorbsiyonlu sistemlerdeki gibi basınç farkı yoktur. Habbecik pompalı absorbsiyonlu soğutma sisteminin basıncı helyum kullanılarak dengelenmektedir. Habbecik pompalı absorbsiyonlu sistem pompa ve kompresör gibi herhangi bir mekanik parça bulundurmaması nedeniyle sessiz çalışmaktadır. Bu sistem sessizliğin istendiği mekanlarda (otel odaları, ofis gibi) yaygın olarak kullanılmaktadır. Bu sebeple bu sistem mini soğutucular, mini barlarda kullanılmaktadır. Genel olarak habbecik pompalı absorbsiyonlu sistemlerin kullanıldığı mini soğutucu ve mini barlarda karşılaşılan en büyük sorun, bu sistemlerin soğutma verimlerinin düşük olmasıdır. Tez çalışmasında yapılan incelemede bu sorun üzerinde durulmuş, sistem performansını etkileyen parametreler deneysel ve termodinamik yönden incelenmiştir. Bu kapsamada tez çalışmasının ikinci bölümünde, absorbsiyonlu sistemler hakkında bilgi verilmiş, habbecik pompalı absorbsiyonlu sistemin ayrıntılı olarak çalışma prensibine değinilmiştir. Mini soğutucu ve mini barlarda kullanılan bu sistem içerisinde üç akışkan (amonyak-su-helyum) dolaşmaktadır. Kaynatıcı bölgesine ısı verilmesiyle amonyak-su karışımından ayrılan amonyak buharı habbecik pompası içinde yükselerek saflaştırıcı kısmına ilerlemektedir. Amonyak buharı içinde bulunan su buharının bu kısımda yoğuşması ile amonyak buharı yoğuşturucuya girip yoğuşmaktadır. Daha sonra buharlaştırıcı kısmına gelen amonyak sıvısı helyum içerisine yayınarak buharlaşmaktadır. Amonyak buharı ve helyum gazının soğurucu kısmına ilerlemesi ve burada amonyak buharının fakir karışım tarafında soğrulması ile elde edilen zengin karışım tekrar kaynatıcı bölgesine geçerek aynı çevrimi tekrarlamaktadır. Tezin üçüncü bölümünde, habbecik pompalı absorbsiyonlu sistemler ile ilgili ayrıntılı literatür çalışması yapılmıştır. Literatür çalışmaları, yapılacak deneysel çalışmalar için başlangıç parametrelerinin belirlenmesi açısından iyi bir referans olmuştur. Habbecik pompalı absorbsiyonlu bir mini barın kabin içi ortalama sıcaklıklarının belirli ortam şartlarında standartlar ile belirlenen değerlerine çekilebilmesi için kabinin toplam ısıl geçirgenliğinin belirlenmesi (UA) gerekmektedir. Bu sebeple tezin dördüncü bölümünde, ters ısı kazancı deneyi yapılmıştır. Daha sonra mini bar sistemine farklı kütlece amonyak derişikliğine sahip karışımlar, farklı helyum basınçlarında şarj edilmiş ve ısı odası testine alınmıştır. Bu testler sonucunda kabin içi ortalama sıcaklıklara bağlı olarak buharlaştırıcı tarafından çekilen ısı bulunmuş, bir günlük zaman diliminde tüketilen enerjiye ise hesap yolu ile ulaşılmıştır. Aynı zamanda bir gün boyunca tüketilen enerji ısı odası testlerinde de ölçülüp, hesaplanan ile kıyaslanarak Soğutma Etkinlik Katsayısı na deneysel yol ile ulaşılmıştır. Tezin beşinci bölümünde ise, farklı basınç ve farklı kütlece amonyak derişikliğine sahip karışımlar ile şarj edilen mini barın ısı odası testleri sonucu ortaya çıkan elemanların sıcaklıkları kullanılarak, termodinamik analiz yapılmıştır. Analiz sonucu, sistem elemanlarından olan ısı kayıp ve kazançlar bulunmuş, sistemin Soğutma Etkinlik Katsayısı termodinamik analiz yoluyla hesaplanmıştır. Daha sonrasında ise, deneysel ve analiz yoluyla çıkan sonuçlar irdelenmiştir. Tezin son bölümünde ise, elde dilen sonuçların kısa bir özeti yapılmış, bu sonuçlar kapsamında sistemde yapılacak iyileştirmeler öneri olarak sunulmuştur.

Most of industrial process uses a lot of thermal energy by burning fossil fuel to produce steam or heat for the purpose. After the processes, heat is rejected to the surrounding as waste. This waste heat can be converted to useful refrigeration buy using a heat operated refrigeration system, such as an absorption refrigeration cycle. Also, absorption systems can work with solar power. Electricity is used from convential vapor compression refrigerators. The use of heat operated refrigeration systems help reduce problems related to global enviromental, such as the so called greenhouse effect from CO2. Another difference between absorption systems and convential vapor compression systems is working fluid used. Most vapor compression systems commonly use chlorofluorocarbon refrigerants (CFCs). CFCs harm the ozone layer that will make absorption systems more attractive. Although absorption systems seem to provide many advanteges, vapor compression systems still dominate all market sectors. In order to promote the use of absorption systems, their performance is required to improve and their cost is required to reduce. The components and principles of operation differences are divided absorption refrigeration systems into many varieties. Conventional absorption refrigeration systems and vapor compression refrigeration systems are quite similar. Unlike vapor compression refrigeration system, compresssor is replaced a complex mechanism consists of absorber, boiler and heat exchanger. Also, the condenser and evaporator of compression refrigeration systems are the same absorption refrigeration systems. Diffusion absorption refrigeration (DAR) is a type of self-circulate absorption systems. In this thesis, DAR systems was investigated. It uses three working fluids, water as an absorbent, ammonia as a refrigerant and helium as an auxiliary gas. Heat is supplied to the pump by electrical. The main characteristic of the DAR is of having no moving parts. These systems are both quiet and reliable. This feature provides advantage in certain locations. For example; hotel rooms, offices etc. A thermally driven pump (generator), which is called bubble pump, acts to circulate the fluid. Differential pressure between the condenser and evaporator is too large to the overcome by the bubble pump. DAR systems have auxiliary inert gas for equalizing the system pressure. The auxiliary inert gas is usually helium. The inert gas plays its role to reduce the partial pressure of ammonia in the evaporator and absorber, so the partial pressure of ammonia is kept low enough to correspond with the temperature required inside the evaporator. These characteristics make the DAR small and simple to be built, but not really efficient with very low coefficient of performance (COP) and, therefore, with high primary energy consumption per unit of heat removed. Generally, mini cooler fridge and beverage coolers use DAR systems for cooling. Over the years, a number of authors have investigated and described the performances of various DAR cycles, graphically, experimantally and numerically. The graphical method has been proposed for calculating heat capacities, concentrations and temperatures in the cycle, applinyg enthalpy-concentration diyagram. This, however allowed developing a partial model only. There are many parameters that determine the DAR cycles efficiency and some of them ammonia mass fraction in solution and system pressure. In this thesis, the DAR cycle s efficiency was examined with respect to experimental and thermodynamic (graphical model). In this context, the second part of thesis gives information about absorption refrigeration systems, espacially DAR. Working prenciple of DAR cycle was discussed in details. DAR systems which are based on ammonia-water-helium as working triplet. In the generator, heat is supplied to the rich. The hot refrigerant and absorbent vapor mixture arises in the capillary and, is separated from the remaining weak liquid solution that returns in the shell of the capillary. The vapor goes through the rectifier and is cooled down to separate most of the absorbent fluid. The remaining near-pure ammonia vapor moves toward the condenser where condenses. Then it flows to the evaporator after a cooling in the gas heat exchanger (gas HX). The uncondensed refrigerant flows to a reservoir through the gas bypass. At the evaporator entrance, the liquid refrigerant reduces its partial pressure as it mixes with the auxiliary inert gas arriving from the absorber through the gas HX. The resulting mixture leaves the evaporator and the following preheating in the gas HX allows the refrigerant to become a saturated vapor. Then, the gas-vapor mixture passes through the reservoir, entering the absorber coil from the bottom by flowing upward in a counter-current arrangement to the weak solution, which enters the absorber through the liquid solution heat exchanger (liquid HX). The refrigerant vapor is absorbed in the weak solution. The resulting rich solution flows to the reservoir. Then it leaves the reservoir toward the generator. The inert gas is not absorbed and returns to the evaporator. The weak solution is reheated in the generator before entering the liquid HX but its temperature is assumed not changed. The third section of the thesis, a detailed study has been done for DAR systems. Most of literature studies have been investigated the DAR systems aspect of experimental and thermodynamic model. Some of literature studies have been focused on different generator configuration and geometry of bubble pump. Also, studies investigated another refrigerants, absorbents and auxiliary gas. Auxiliary gas both helium performance is higher than hydrogen performance. It is known that hyrogen can cause danger if it leaks. As well, the most common working fluids are water/NH3 and LiBr/water. Preference for ammonia, it has a high latent heat vaporization, which is neccessary for efficient performance of the system. It can be used for low temperature applications, as the freezing point of ammonia is -77⁰C. As a consequence of literatures studies, COP changes between 0.1-0.3 and rich solution concentration must between 0.25-0.3. For generator temperatures between 195⁰C and 205⁰C, recommended values for ammonia concentrations of the rich and weak solutions were 0.3 and 0.1 respectively. Ammonia has better performance than another refrigerants for cooling. It is found that for the same heat input the highest COP obtained when the generator heat input is applied directly into the rich solution and heat recovered by the bubble pump tube. Literature studies have been a good reference for determining the inital parameters which are essential for experimental studies. In the fourth part of thesis are given information about experimantal studies. First of all, The overall heat transfer coefficient of cabin, which has relationship between resistance (UA), must be known to keep the average standard temperature of the interior of a absorption mini cooler. For finding this value, reverse heat leak test was set. Then, DAR system is charged with ammonia-water mixtures. This mixtures have different mass fraction of ammonia and the initial pressure of DAR system is helium charging pressure. After charging, the system works and ammonia-water vapor pressure rises. Thus, system pressure is bigger than initial pressure. As a result of these tests, how much heat was absorbed by the evaporator is calculated using UA and the difference between the average cabin temperature and the ambient temperature. So, one-day time period energy consumption was found experimentally. At the same time, the amount of energy consumption during the tests was measured daily. The ratio of calculated and measured daily energy consumptions gives COP experimentally. Thermodynamic model of DAR system was established in the fifth chapter of thesis. Solution concentrations and partial pressures of DAR system s components were found graphically. The components temperature are measured by termocouple experimentally. Enthalpies of the fluid moving within the system were found by correlations equations of entalpy with Matlab. These enthalpies were used in equations of conversation of mass and equations of conservation of energy for calculating the components heat loses and gains. Then, COP is found. Consequentially, thermodynamic model and experimantal results are compared. In the last part of thesis gives a brief summary of results and these results are put forward as a proposal within the scope of improvements to the system.
Thermodynamic Analysis Of Diffusion Absorption Refrigeration Systems
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2012
Keywords: absorbsiyonlu soğutma; habbecik pompası; amonyak-su karışımı; absorption refrigeration; bubble pump; diffusion; ammonia-water